Host-pathogen interaction in arthropod vectors: Lessons from viral infections - Perveen, Nighat; Muhammad, Khalid; Muzaffar, Sabir Bin; Zaheer, Tean; Munawar, Nayla; Gajic, Bojan; Sparagano, Olivier Andre; Kishore, Uday; Willingham, Arve Lee (Frontiers in Immunology, 2023)
Haematophagous arthropods can harbor various pathogens including viruses, bacteria, protozoa, and nematodes. Insects possess an innate immune system comprising of both cellular and humoral components to fight against various infections. Haemocytes, the cellular components of haemolymph, are central to the insect immune system as their primary functions include phagocytosis, encapsulation, coagulation, detoxification, and storage and distribution of nutritive materials. Plasmatocytes and granulocytes are also involved in cellular defense responses. Blood-feeding arthropods, such as mosquitoes and ticks, can harbour a variety of viral pathogens that can cause infectious diseases in both human and animal hosts. Therefore, it is imperative to study the virus-vector-host relationships since arthropod vectors are important constituents of the ecosystem. Regardless of the complex immune response of these arthropod vectors, the viruses usually manage to survive and are transmitted to the eventual host. A multidisciplinary approach utilizing novel and strategic interventions is required to control ectoparasite infestations and block vector-borne transmission of viral pathogens to humans and animals. In this review, we discuss the arthropod immune response to viral infections with a primary focus on the innate immune responses of ticks and mosquitoes. We aim to summarize critically the vector immune system and their infection transmission strategies to mammalian hosts to foster debate that could help in developing new therapeutic strategies to protect human and animal hosts against arthropod-borne viral infections.